2015
DOI: 10.1002/pssc.201400167
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature hollow cathode plasma‐assisted atomic layer deposition of crystalline III‐nitride thin films and nanostructures

Abstract: Hollow cathode plasma-assisted atomic layer deposition (HCPA-ALD) is a promising technique for obtaining III-nitride thin films with low impurity concentrations at low temperatures. Here we report our previous and current efforts on the development of HCPA-ALD processes for III-nitrides together with the properties of resulting thin films and nanostructures. The content further includes nylon 6,6-GaN core-shell nanofibers, proof-of-concept thin film transistors and UV photodetectors fabricated using HCPA-ALD-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…41 Previously, we had reported refractive index value of 2.55 at 650 nm for a ∼20 nm InN thin film grown by HCPA-ALD at the same substrate temperature but non-optimized growth conditions. 33 This shows that, with the increase in thickness of InN from 20 to 48 nm, refractive index increased from 2.55 to 2.66 at 650 nm. This improvement might be attributed to film densification with the increase in thickness of the film.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…41 Previously, we had reported refractive index value of 2.55 at 650 nm for a ∼20 nm InN thin film grown by HCPA-ALD at the same substrate temperature but non-optimized growth conditions. 33 This shows that, with the increase in thickness of InN from 20 to 48 nm, refractive index increased from 2.55 to 2.66 at 650 nm. This improvement might be attributed to film densification with the increase in thickness of the film.…”
Section: Resultsmentioning
confidence: 83%
“…However, in the case of InN (deposited using non-optimized parameters), we had found that addition of H 2 plasma with N 2 plasma as second precursor resulted in InN films with poor crystalline quality showing high level of impurities with significant voids in the films, resulting in low-density films. 33 This profound effect of H 2 plasma was attributed to plasma-related deterioration during the growth. In that context, present results illustrate that N 2 -only plasma exposure time is critical in removing the carbon containing ligands of TMI and results indicate that higher N 2 plasma exposure time is necessary to obtain InN films with minimum amount of carbon incorporation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…% oxygen) incorporation, whereas the film deposited using N 2 plasma reveals a single phase h-InN with substantially low impurity (<2% oxygen) content. 19 In this work, we have carried out growth of InN at 450 C with N 2 /H 2 plasma as nitrogen source, and no film growth was observed. Therefore, N 2 plasma was used as nitrogen source for the growth of InN film while N 2 /H 2 plasma was used as nitrogen source for the growth of GaN film at 450 C. Metal and nitrogen precursors for growth of InN, BN, and GaN are summarized in Table I.…”
Section: Resultsmentioning
confidence: 98%
“…27 However, PL measurement from InN samples did not exhibit considerable emission. In addition to defect bands at lower wavelength, broad spectral features are visible with peaks centered at 508, 618, and 671 nm for In 0.25 Ga 0.75 N, In 0.33 Ga 0.67 N, and In 0.64 Ga 0.36 N thin films, respectively.…”
Section: View Article Onlinementioning
confidence: 96%